2019
DOI: 10.5312/wjo.v10.i4.176
|View full text |Cite
|
Sign up to set email alerts
|

Investigational growth factors utilized in animal models of spinal fusion: Systematic review

Abstract: BACKGROUND Over 400000 Americans annually undergo spinal fusion surgeries, yet up to 40% of these procedures result in pseudoarthrosis even with iliac crest autograft, the current “gold standard” treatment. Tissue engineering has the potential to solve this problem via the creation of bone grafts involving bone-promoting growth factors ( e.g ., bone morphogenetic protein 2). A broad assessment of experimental growth factors is important to info… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 67 publications
0
9
0
Order By: Relevance
“…This technique aims to fuse two or more vertebrae together in order to treat medical conditions that arise from degenerative, traumatic and oncologic pathologies. However, pseudarthrosis or failed fusion rates are reported to be as high as 40% in primary spinal fusion surgery and up to 60% in revision cases [128], which leads to the need for the improvement of new spinal fusion materials and their evaluation through preclinical models (Table 4). Critical-sized segmental defects are generally defined by considering the diameter of the shaft multiplied by factor 2.0-2.5 [120,121], although some studies report the use of defects three times larger than the diameter of the bone [120].…”
Section: Selection Of Implantation Sitementioning
confidence: 99%
See 2 more Smart Citations
“…This technique aims to fuse two or more vertebrae together in order to treat medical conditions that arise from degenerative, traumatic and oncologic pathologies. However, pseudarthrosis or failed fusion rates are reported to be as high as 40% in primary spinal fusion surgery and up to 60% in revision cases [128], which leads to the need for the improvement of new spinal fusion materials and their evaluation through preclinical models (Table 4). Critical-sized segmental defects are generally defined by considering the diameter of the shaft multiplied by factor 2.0-2.5 [120,121], although some studies report the use of defects three times larger than the diameter of the bone [120].…”
Section: Selection Of Implantation Sitementioning
confidence: 99%
“…This technique aims to fuse two or more vertebrae together in order to treat medical conditions that arise from degenerative, traumatic and oncologic pathologies. However, pseudarthrosis or failed fusion rates are reported to be as high as 40% in primary spinal fusion surgery and up to 60% in revision cases [128], which leads to the need for the improvement of new spinal fusion materials and their evaluation through preclinical models (Table 4). Several studies have shown striking similarities between the spine of humans and quadrupeds, not only in the osseous structural arrangement (suggesting that quadruped and biped spines experience similar loads), but also in mechanical properties of specific spinal segments [133,134].…”
Section: Selection Of Implantation Sitementioning
confidence: 99%
See 1 more Smart Citation
“…To address these issues, extensive work has been performed over the past several decades, creating the field of bone tissue engineering, which comprises all efforts aimed at creating implantable bone substitutes[ 9 ]. In their most basic form, bone tissue engineering products constitute a biological scaffold to facilitate new bone growth often combined with bioactive molecules and/or cells that induce new bone formation[ 9 - 11 ]. One prime example is the Infuse ® Bone Graft (Medtronic Spinal & Biologics; Memphis, TN) – a collagen sponge with adsorbed recombinant human bone morphogenetic protein-2 (rhBMP-2)[ 12 ] that has been used in more than a million neurosurgical and orthopaedic patients since receiving Food and Drug Administration (FDA) approval in 2002[ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…tein-2), 27,43,76 mesenchymal stem cells, 79 novel bone graft substitutes, 31,73 and dynamic instrumentation. 65,91 Postoperative electrical stimulation therapy has also been suggested as an attractive adjuvant therapy to enhance or accelerate bony union.…”
mentioning
confidence: 99%